Verification and validation of MPS potential force interface tension model for stratification simulation. (1st December 2020) - Zhu, Yingzi; Qiu, Zhifang; Xiong, Jinbiao; Yang, Yanhua
Highlights: Potential-force surface tension model is extended to simulate interface deformation between immiscible fluids. The interface tension model is verified to reproduce contact angles. The interface tension model is validated with stratification experiments. Abstract: The moving particle semi-implicit (MPS) method is employed to simulate the density stratification of immiscible fluids. For the sake of accurate prediction of immiscible fluids, the potential-force surface tension model is extended to calculate the interface tension. The interface tension model is verified by the simulation of a floating droplet and shows accurate prediction of the contact angle between immiscible fluids. In order to demonstrate the validity of the interface tension model at the solid surface, the wall contact angle with immiscible fluids is simulated and the predicted value agrees well with the theoretical value. In order to further validate the modified MPS method, the two-dimensional dam-break stratification experiment is simulated. The validation shows that the interface deformation can be accurately reproduced by the interface tension model. Finally, three-dimensional injection stratification is simulated to prove the effectiveness of implemented modification.